Nucleotide sequences and properties of the sites involved in lysogenic insertion of the bacteriophage HP1c1 genome into the Haemophilus influenzae chromosome. - Waldman, A S (1987)
Bacteriophage HP1c1 lysogenizes its host Haemophilus influenzae Rd by inserting its genome into the bacterial chromosome. The DNA segments corresponding to the integration regions on the phage and host chromosomes and the two junctions formed between phage and host sequences on lysogenic insertion were isolated and propagated in Escherichia coli HB101 as hybrid plasmids by using pBR322 as the vector. The nucleotide sequences in the vicinity of the point of recombinational insertion were determined. Phage and host DNA shared an extensive, nearly identical, segment that was 183 base pairs long. This segment consisted of 93 identical residues and a 27-residue portion containing 6 mismatches, followed by 63 identical residues. Recombinational insertion occurred within the 63-residue identical segment and involved neither duplication nor deletion of any residues. Short inverted repeats consisting of clustered A-T base pairs were present within the two 27-residue segments. Two additional sites on the host chromosome showed significant hybridization to the phage-host homology region.